Asian corn borer (Ostrinia furnacalis Guenee) oviposition preferences on maize (Zea mays Linn), king grass (Panicum maximum Jacq.), and cogon grass (Imperata cylindrica (L.) - Yosefus F. da-Lopez; Y. Andi Trisyono; Witjaksono Witjaksono (Jurnal Entomologi Indonesia, 2020)
Insects’ oviposition behavior on alternate host plants is very helpful to understand the interaction between host plants and insects, the dynamics of insect populations, and the effectiveness of alternate host plants as refugia in managing insect resistance. The oviposition preference of Ostrinia furnacalis on maize (Zea mays L), king grass (Panicum maximum Jacq.), and cogon grass (Imperata cylindrica (L.) was studied through no-choice test, two-choice test, and three-choice test. The oviposition preferences hierarchy of O. furnacalis on maize, king grass, and cogon grass wass sequentially maize > king grass > cogon grass when the tested plants were at 21 DAP (days after planting). However, the hierarchy pattern may change depending on host plants phenology. The 35-day-old king grass was more preferred by O. furnacalis (proportion of eggs = 0.692; OPI = 37.57) than maize (proportion of eggs = 0.301; OPI = -38.780) and cogon grass (proportion of eggs = 0.174; OPI = -65.183) for oviposition. These findings indicated that king grass was a potential alternate host for O. furnacalis to survive and could serve as refugia in IRM strategy. However, it needs further research in the field to ensure the potential of king grass as refugia for O. furnacalis.